Keabsahan Transaksi Jual Beli Cash and Delivery (COD) Oleh Anak Di Bawah Umur Di Platform E-Commerce - Gangga Listiawan (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
This study examines the validity of buying and selling transactions using the Cash on Delivery (COD) payment method involving minors on e-commerce platforms. The primary focus of this research is the aspect of legal capacity in online transactions based on Article 1320 of the Indonesian Civil Code (KUHPerdata), which requires legal capacity as an essential element of a valid agreement. Minors, as regulated in Article 330 of the Civil Code, are considered not to have full legal capacity to enter into binding agreements. However, in practice, children frequently engage in online transactions without strict age verification mechanisms. The findings indicate that while such transactions may be considered valid if no party disputes them, the legal capacity of minors remains a legal issue that can create uncertainty. In cases of dispute, a minor’s incapacity may serve as grounds for requesting contract annulment. To mitigate this risk, stricter regulations and age verification mechanisms in e-commerce COD transactions are necessary. Marketplaces must be responsible for providing features that allow parental or guardian involvement. Additionally, consumer education is essential to raise awareness of the legal risks that minors may face.